Factores que inciden en la sostenibilidad de los emprendimientos en el cantón Las Naves, provincia Bolívar 2015–2016 - Armijo Bastidas, Justo Marcelo (2016)
The aim of this research is to identify sustainability factors of projects to help people who wish to start enterprises or those who own some to be able to undertake risks that can run if they are not corrected on time because even in this moment someone should be thinking of some great business idea but, nevertheless, it is not the same as having it in mind as to make it in the reality. For those people who like to seize opportunities but might not have a study to reveal those factors that will help their venture be successful, here, it is a study focusing on the urban area of Las Naves city, Bolívar Province presented. First, it was made a diagnosis of the enterprises of Las Naves town. Secondly to identify the factors affecting the sustainability of projects. From this, survey was applied to three segments of different people: who wish, who possess and who failed, with their venture. In order to observe different aspects, features, knowledge and skills of entrepreneurs were developed to post them to an appraisal, showing the impact certain factors in the sustainability of enterprises. Finally, from the assessment and comparison of factors of the three segments of people, the key and critical factors which help to avoid mistakes and rethink projects that have greater chance of success those entrepreneurs of Las Naves city were determined. According to the research, key factors could be determined, while were those outstanding in order to maintain the undertakings as they are compromised with the family and with yourself, resignation, sacrifice total giving to the enterprise; perseverance, attention quality to the client, reputation, among others. Critic factors, low law knowledge regulations, and some other documents, about business taking, risk perception, taxes, and business figure.